OPTIMISM FOR INDONESIA'S ECONOMY IN 2026: CHALLENGES AND OPPORTUNITIES - Surya, Ruswiati; Irianto, Bambang S. (SYNTIFIC, 2025)
Background. Entering 2026, Indonesia’s economy faces a complex global environment characterized by geopolitical uncertainty, fluctuating commodity prices, and the tightening of monetary policies in advanced economies. These external pressures pose significant challenges for developing countries, including Indonesia. Nevertheless, Indonesia demonstrates a relatively optimistic economic outlook, supported by stable macroeconomic conditions, controlled inflation, and the continuity of structural reforms implemented in recent years. Research Purpose. This study aims to examine the optimism surrounding Indonesia’s economy in 2026 by analyzing both the challenges and opportunities that shape national economic performance. Research Method. This study used a qualitative approach with a library research method. The analysis highlights several key drivers of economic optimism, including prudent fiscal policy, adaptive monetary measures, industrial downstreaming, increased investment, and the rapid growth of the digital economy. Findings. In addition, Indonesia’s demographic bonus and commitment to sustainable development through green and blue economy initiatives provide strategic opportunities to enhance productivity and long-term economic growth. However, this optimism must be balanced with a realistic assessment of existing challenges. Structural issues such as regional development disparities, uneven quality of human resources, reliance on primary commodities, and vulnerability to global financial volatility remain critical concerns. These challenges require comprehensive and integrated policy responses to ensure that economic growth is not only robust but also inclusive and sustainable. Conclusion. Indonesia’s economic optimism in 2026 depends on the government’s ability to address structural constraints and effectively capitalize on emerging opportunities.